Perancangan dan Pembuatan Sistem Administrasi Pada Toko kiddy Baby Shop - Ivan Surya Sutjianto; Agustinus Noertjahyana; Silvia Rostianingsih (Jurnal Infra, 2017)
Effectivity and efficiency is one of the most needed factory by human, it is because of their growing activity to do their business. This is surely increase the human needs of more effective and efficient technology. There are so many business that have already harness the technology advances, it can be clarified from the business transaction that are computerized. Because technology usage can help business to work effectively and efficiency.From the background above Kiddy Baby Shop tried to improve their effectiveness and efficiency from their business process by making a web application. Hopefully, this website could ease the administration process that are happening in Kiddy Baby Shop. All the feature such as purchase, sale, and report can be accessed from one system so it will decrease the human error risk.This research conducted with some interview and observation, the goal of these activity is to gather the information needed by this research. From all of the information gathered, Data Flow Diagram (DFD), Database Design, and Entity Relationship Diagram (ERD) will be built. All of the diagram built will become the foundation for building the web application.From the conducted research, administration web application built already fulfill the basic needs of the user. User can feel the effectiveness and efficiency in the Kiddy Baby Shop administration data processing process.